Stereotactic body radiotherapy plus transcatheter arterial chemoembolization for inoperable hepatocellular carcinoma patients with portal vein tumour thrombus: A meta-analysis. - Xiao-Fei Zhang; Lin Lai; Hui Zhou; Yuan-Jun Mo; Xu-Quan Lu; Min Liu; Yun-Xin Lu; En-Cun Hou (PLoS ONE)
Background The efficacy and safety of stereotactic body radiotherapy (SBRT) plus transcatheter arterial chemoembolization (TACE) versus SBRT or TACE alone(monotherapy) for hepatocellular carcinoma (HCC) patients with portal vein tumour thrombus (PVTT) remains controversial. This meta-analysis was performed to provide more powerful evidence for clinical strategies in inoperable HCC with PVTT. Methods We searched the PubMed, EMBASE, Web of Science, Cochrane Library, China Biology Medicine (CBM), China National Knowledge Infrastructure (CNKI), VIP Journal Integration Platform (VIP), and WanFang databases for eligible studies. We pooled the results of 1- and 2-year overall survival rates (OSRs), objective response rates (ORRs), and adverse events (AEs) between the two groups and performed a subgroup meta-analysis for study type, control group, treatment order, and the interval between SBRT and TACE. Results Nine studies with 10 cohorts involving 938 patients were included in our meta-analysis. SBRT plus TACE yielded significantly higher 1-year OSR (RR, 1.52[95% CI, 1.33-1.74]), 2-year OSR (RR, 2.00 [95% CI: 1.48-2.70]), ORR (RR = 1.22 [95% CI, 1.08-1.37]), and a lower progression disease (PD) rate (RR = 0.45 [95% CI:0.26-0.79]) than monotherapy. No significant differences were detected in CR, PR, SD, or AEs between the two groups. Subgroup analysis regarding study type, control group, and treatment order indicated that compared with monotherapy, the combination of SBRT with TACE was associated with an increase in 1- and 2-year OSRs but not in ORR. In regard to the interval between SBRT and TACE, subgroup analysis found that the combination therapy for patients with an SBRT-TACE interval <28 days was preferable to monotherapy in the 1- and 2-year OSRs, and ORR. However, for patients with an SBRT-TACE interval ≥28 days, no obvious distinctions were observed in the 1-year OSR, 2-year OSR, or ORR between the two groups. Conclusion The combination of SBRT with TACE appears to be better than monotherapy in treating HCC with PVTT and should be recommended for inoperable HCC patients with PVTT.